2021
DOI: 10.3389/fmicb.2021.714651
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering Diagnostic Value of Mitogenome for Identification of Cryptic Species Fusarium graminearum Sensu Stricto

Abstract: Fungal complexes are often composed of morphologically nearly indistinguishable species with high genetic similarity. However, despite their close relationship, they can exhibit distinct phenotypic differences in pathogenicity and production of mycotoxins. Many plant pathogenic and toxigenic fungi have been shown to consist of such cryptic species. Identification of cryptic species in economically important pathogens has added value in epidemiologic studies and provides opportunities for better control. Analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…This strain is held in the fungal collection Westerdijk Fungal Biodiversity Institute (Utrecht, Netherlands) as F. graminearum and according to available metadata it was isolated from maize in South Africa where F. boothii has been frequently reported (van der Lee et al, 2015). However, our previous mitochondrial-based comprehensive studies did not indicated incorrect taxonomic status of this strain (Kulik et al, 2015;Brankovics et al, 2018;Wyre " bek et al, 2021). The complete mitogenome of CBS 119800 (NCBI accession no.…”
Section: Genomic Samplingmentioning
confidence: 82%
See 2 more Smart Citations
“…This strain is held in the fungal collection Westerdijk Fungal Biodiversity Institute (Utrecht, Netherlands) as F. graminearum and according to available metadata it was isolated from maize in South Africa where F. boothii has been frequently reported (van der Lee et al, 2015). However, our previous mitochondrial-based comprehensive studies did not indicated incorrect taxonomic status of this strain (Kulik et al, 2015;Brankovics et al, 2018;Wyre " bek et al, 2021). The complete mitogenome of CBS 119800 (NCBI accession no.…”
Section: Genomic Samplingmentioning
confidence: 82%
“…Our previous large scale sequencing project was launched in order to obtain genome sequences from a large collection of strains of the pandemic pathogen Fusarium graminearum sensu stricto ( F.g. ) ( Wyrebek et al, 2021 ). This cryptic species is mainly responsible for two cereal diseases: Fusarium Head Blight (FHB) of wheat and barley and Fusarium Ear Rot (FER) of maize.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial genomes evolve independently of and faster than the nuclear genome [10]. Mitogenomes have also been proposed as a useful tool for diagnostic purposes in Fusarium species [11]. The concept of using mitogenome diversity for the identification of species mainly derives from their higher DNA copy number compared with nuclear DNA, and hence the high recovery and amplification success in eukaryotes where insufficient phylogenetic signals have accumulated in nuclear genes [12].…”
Section: Introductionmentioning
confidence: 99%